2022
DOI: 10.1007/s12032-021-01590-y
|View full text |Cite
|
Sign up to set email alerts
|

IL-33 induces ADAMTS5 expression and cell migration in glioblastoma multiforme

Abstract: Glioblastoma multiforme (GBM), characterized by a high rate of proliferation and migration capacity, is an incurable brain tumor in adults. , a member of the IL-1 cytokine superfamily and a disintegrin and metalloproteinase with thrombospondin motifs 5 (ADAMTS5), a family of zinc dependent metalloproteinases are known to have an essential roles in GBM migration and invasion. Previous studies have separately revealed elevated expressions of IL-33 and ADAMTS5 in GBM; however, the interaction between IL-33 and AD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 46 publications
(39 reference statements)
0
3
0
Order By: Relevance
“…Moreover, numerous studies have identified that IL-33 has a dual function as a coordinator of the glioblastoma microenvironment, which ultimately contributes to tumorigenesis [37][38][39][40]. Its nuclear and secreted functions may promote chemokine recruitment and activate innate immune cells, establishing a pro-tumorigenic environment in glioblastoma [38].…”
Section: Il-33/st2 Axis and Neuroinflammationmentioning
confidence: 99%
“…Moreover, numerous studies have identified that IL-33 has a dual function as a coordinator of the glioblastoma microenvironment, which ultimately contributes to tumorigenesis [37][38][39][40]. Its nuclear and secreted functions may promote chemokine recruitment and activate innate immune cells, establishing a pro-tumorigenic environment in glioblastoma [38].…”
Section: Il-33/st2 Axis and Neuroinflammationmentioning
confidence: 99%
“…Meanwhile, IL-1b also activates the p38 mitogen-activated protein kinase (MAPK)activated protein kinase 2 (MK2)-human antigen R (HuR), tolllike receptor 4 (TLR-4), and other inflammation-associated signaling pathways that significantly increase the levels of IL-6 and IL-8 in GBM tumor cells, eventually developing an inflammatory TME in favor of GBM invasion and growth (61)(62)(63). Additionally, IL-33 induced by GBM tumor cells is another important inflammatory mediator that accelerates GBM proliferation, migration, and invasion (47,64,65). Interestingly, IL-33 could transform non-stem cells to GBM stem cells (66), activate disintegrin and metalloproteinase with thrombospondin motifs 5 (ADAMTS5) and EGFR by promoting the accumulation of tenascin-C (TNC), which in turn exacerbates GBM tumor cell proliferation (47,64,65,67).…”
Section: Gbm Tumor Cells Promote Inflammationmentioning
confidence: 99%
“…Additionally, IL-33 induced by GBM tumor cells is another important inflammatory mediator that accelerates GBM proliferation, migration, and invasion (47,64,65). Interestingly, IL-33 could transform non-stem cells to GBM stem cells (66), activate disintegrin and metalloproteinase with thrombospondin motifs 5 (ADAMTS5) and EGFR by promoting the accumulation of tenascin-C (TNC), which in turn exacerbates GBM tumor cell proliferation (47,64,65,67). Both subfamilies of IL-1 accelerate GBM relapse, however, blocking IL-1b and IL-33 can reduce tumor progression-associated compensation mechanisms including the Warburg effect (47,68).…”
Section: Gbm Tumor Cells Promote Inflammationmentioning
confidence: 99%